Experimental study of the γ-surface of austenitic stainless steels. (July 2019) - Molnár, Dávid; Engberg, Göran; Li, Wei; Lu, Song; Hedström, Peter; Kwon, Se Kyun; Vitos, Levente
Abstract: We introduce a theory-guided experimental approach to study the γ-surface of austenitic stainless steels. The γ-surface includes a series of intrinsic energy barriers (IEBs), which are connected to the unstable stacking fault (USF), the intrinsic stacking fault (ISF), the unstable twinning fault (UTF) and the extrinsic stacking fault (ESF) energies. The approach uses the relationship between the Schmid factors and the effective energy barriers for twinning and slip. The deformation modes are identified as a function of grain orientation using in situ electron backscatter diffraction measurements. The observed critical grain orientation separating the twinning and slip regimes yields the USF energy, which combined with the universal scaling law provides access to all IEBs. The measured IEBs and the critical twinning stress are verified by direct first-principles calculations. The present advance opens new opportunities for modelling the plastic deformation mechanisms in multi-component alloys. Graphical abstract: Image 1